Using metis model to solve the torsion problem of a prismatic bar - Duong, Nguyen Tien; Hung, Nguyen Dang (Vietnam Journal of Mechanics, 2005)
Based on Lekhnitskiis elasticity theory [1], the formulae of generalized plane strain state for the torsion problem of a prismatic bar are established. By this way, this problem in 3 dimensions (3D) is transformed into the problem in 2.5D. Metis models [3] constitute a bridge between the classical models in one field and the hybrid models in two fields. They have the advantage properties of two parents: the dual and monotonous properties of the pure models and the fast convergence of hybrid models. This paper uses the metis displacement model to solve the torsion problem of a prismatic bar after transform this problem from 3D into 2.5D. The agreement of the results in this method with those in exact solution by the analytical method indicated the exactitude of this new model.